El envejecimiento de la población en Cuba - Hernández Castellón, Raúl (El Colegio de México A.C., 1992)
This article presents a brief discussion of the primary aspects associated with aging of the Cuban population, from a demographic, socioeconomic and political perspective.The first issue discussed in the article is how international immigration has contributed to the aging process of the country's population, and the possible causes of this immigration.The author briefly analyzes the evolution of demographic transitions in Cuba. At the same time, he points out the efforts that the country is making to deal with an accelerated increase in the sixties-plus population and the solutions that have been found to meet the challenge, as well as methodological aspects related to the issue of aging. It is important to note that the elderly currently constitute 12% of the Cuban population.